2003
DOI: 10.1023/a:1024508927361
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Of several types of chemical surfactants and biosurfactants, only the culture broth of Bacillus subtilis C1 containing surfactin at 10 mg l(-1) completely inhibited the growth of Microcystis aeruginosa, a bloom-forming cyanobacterium in highly eutrophic lakes. The broth with 10 mg surfactin l(-1) also removed 85% of the maximally grown M. aeruginosa (chlorophyll-a concentration, 1000 microg l(-1)) within 2 d, and the removal efficiency was enhanced by Ca2+ over 1 mM. The growth of Anabaena affinis, another blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Most algicidal bacteria isolated from the environment are characterized as belonging to the genera Cytophaga, Saprospira, Pseudoalteromonas, and Alteromonas (55). Recently, other studies have confirmed that some species of Bacillus, such as B. subtilis and B. fusiformis, can inhibit the growth of M. aeruginosa (18,19). In the present study, we showed that 24 Bacillus strains exerted bactericidal activity against M. aeruginosa.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Most algicidal bacteria isolated from the environment are characterized as belonging to the genera Cytophaga, Saprospira, Pseudoalteromonas, and Alteromonas (55). Recently, other studies have confirmed that some species of Bacillus, such as B. subtilis and B. fusiformis, can inhibit the growth of M. aeruginosa (18,19). In the present study, we showed that 24 Bacillus strains exerted bactericidal activity against M. aeruginosa.…”
Section: Discussionsupporting
confidence: 67%
“…can suppress the growth of harmful algal bloom species (9,18,19). In a previous study, Ahn et al (18) revealed that the culture broth of Bacillus subtilis C1 containing 10 mg liter Ϫ1 surfactin completely inhibited the growth of M. aeruginosa, although these researchers did not further isolate the surfactin from the culture broth or construct a mutant to verify its inhibitory activity. As such, the active compound(s) and mechanisms of action remain to be identified.…”
mentioning
confidence: 99%
“…The joint toxicity effect of the PFOS and ZnO-NPs exposure could be explained in terms of interactions between the Zn 2+ and the surfactants. Based on the structural characteristics of the PFOS and ZnO-NPs, the potential reasons and mechanism hypotheses are as follows: the surfactants may damage the membranes by perturbing the lipid bilayers [50,51]. Therefore, nanoparticles penetrated through cell membranes easier and caused more serious damage to zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ]. These algicidal bacteria inhibit the growth of harmful algae by attacking the cells either directly via cell-to-cell contact or indirectly via the release of algicdal substances [ 11 , 12 ], including proteases [ 13 ], peptides [ 14 ], bio-surfactants [ 15 , 16 ], amino acids [ 17 ] and antibiotics [ 18 ]. However, few purified compounds have been identified.…”
Section: Introductionmentioning
confidence: 99%